Germany : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Securities Regulation, Insurance Regulation, Monetary and Financial Policy Transparency, Payment Systems, and Securities Settlement. (IMF Staff Country Reports; Country Report ;, 2003)
The German financial system is complex and highly diversified. The second most important class of financial institutions is insurance and pension companies. Germany has taken steps to enhance accounting and auditing practices and to align corporate governance with best international practices. The German banking system is resilient, but relevant indicators show some deterioration. The main vulnerability facing all sectors of the insurance industry is the pressure on capital ratios and risk-bearing capacity from the poor performance of investment portfolios. Securities regulation is of a high standard.